The ferret as a model organism to study influenza A virus infection - Jessica A. Belser; Jacqueline M. Katz; Terrence M. Tumpey (The Company of Biologists, 2011)
Influenza is a human pathogen that continues to pose a public health threat. The use of small mammalian models has become indispensable for understanding the virulence of influenza viruses. Among numerous species used in the laboratory setting, only the ferret model is equally well suited for studying both the pathogenicity and transmissibility of human and avian influenza viruses. Here, we compare the advantages and limitations of the mouse, ferret and guinea pig models for research with influenza A viruses, emphasizing the multifarious uses of the ferret in the assessment of influenza viruses with pandemic potential. Research performed in the ferret model has provided information, support and guidance for the public health response to influenza viruses in humans. We highlight the recent and emerging uses of this species in influenza virus research that are advancing our understanding of virus-host interactions.